Antimicrobial resistance (AMR) - Amann, Steffen (Eur J Hosp Pharm, 2019)
The position paper of the European Association of Hospital Pharmacists (EAHP) highlights the importance of the prudent use of antimicrobial drugs through antibiotic stewardship to ensure efficient therapy for patients with life-threatening infections. EAHP calls on national governments and health system managers to utilise the specialised background and knowledge of the hospital pharmacist in multi-professional antibiotic stewardship teams. In addition, the paper recommends the universal application of infection prevention and control measures among healthcare professionals. Due to the lack of funding, EAHP urges increased investment to support the development of innovative proposals and the encouragement of practice-based research projects to investigate new fields of infectious disease control such as immunotherapy and to optimise the cost-effectiveness of systems for surveillance on antibiotic use and resistance. In relation to the ‘One Health approach’ of the European Commission, EAHP strongly supports regulatory oversight and proper implementation of measures in the veterinary and agriculture sectors at European, national and local level.